Does Temperature Matter? Case Study of International Tourist Arrivals in Indonesia - Supiandi Supiandi; Muhamad Zaril Gapari; Muhammad Azizurrohman; Riduan Mas’ud; Putrawan Habibi (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Climate is one of several elements that can impact tourist decisions when deciding where to go on vacation. The climate of a country can influences the desirability of a trip in either a favorable or bad way. However, few studies look at the impact of temperature on tourist decisions, particularly in Indonesia. The purpose of this research is to demonstrate the impact of temperature on the arrival of foreign tourists in Indonesia. In the period 2017-2019, the authors used panel data from 168 countries of origin of tourists. To ensure that the research findings were consistent, all models were used, including the Ordinary Least Square, Fixed Effect Model, and Random Effect Model. The findings reveal that the temperature of a tourist's home country has a detrimental impact on their arrival in Indonesia. GDP per capita and the population of the nation of origin have a beneficial effect on foreign tourist arrivals as control factors. Distance, on the other hand, has a detrimental impact.